The Role of Job Satisfaction in Mediating the Effects of Organizational Justice and Work Experience on Employee Performance at Dwaraka The Royal Villas, Ubud, Gianyar - Sugiati, Gusti Ayu; Putri, Ni Putu Viska Widia; Sariani, Ni Ketut (Journal of Governance, Taxation and Auditing, 2026)
This study aims to analyze the influence of organizational justice and work experience on employee performance, (2) the influence of organizational justice and work experience on job satisfaction, (3) the influence of job satisfaction on employee performance, and (4) the role of job satisfaction in mediating the influence of organizational justice and work experience on employee performance. This study was conducted at Dwaraka The Royal Villas, Ubud, Gianyar, with a research sample of 54 respondents taken using saturated sampling techniques. All data were obtained from questionnaire distributions that had been tested for validity and reliability and were suitable for use. The data analysis technique uses PLS-SEM (Partial Least Squares Structural Equation Modeling). The results of the study show that: 1) Organizational justice has a positive and significant effect on employee job satisfaction, 2) Organizational justice has a positive and significant effect on employee performance, 3) Work experience has a positive and significant effect on employee job satisfaction, 4) Work experience has a positive and significant effect on employee performance, 5) Job satisfaction has a positive and significant effect on employee performance, 6) Job satisfaction partially mediates the effect of organizational justice on employee performance, 7) Job satisfaction does not mediate the effect of work experience on employee performance.